Application of Process Tracing Method in Organizational and Management Research - Mohammad Hadi Ranjbar; Bahman Hajipour; Hamidreza Yazdani (روش شناسی علوم انسانی, 2022)
Researchers in the field of organization and management, generally conduct research with the aim of describing or explaining a phenomenon. Clearly, in researches aimed at explanation, it is important to identify the causal chains that create a phenomenon. Since the discovery of correlations between two variables, which is a common method in quantitative research, cannot indicate the existence or absence of causal relationships, taking a qualitative approach and, in particular, the case study method is recommended to researchers. In this research, while introducing the process tracing method, which is one of the most important tools of causal inference in qualitative research and case study, an attempt is made to describe its various techniques and the capacities resulting from the application of this method. Since, the executive mechanism of the process tracing method, unlike statistical models or even other issues related to qualitative methods, has not been studied much, at the end of this study, the method of applying and implementing this method is examined.